An overview of conflicts in supply chain systems. Issue 3 (1st January 2012) - John, Franklin R.; Prasad, P.S.S.
Supply chains are generally complex and are characterised by numerous activities spread across multiple functions and organisations, which pose interesting challenges for effective supply chain coordination. Coordinating and managing distributed entities in a supply chain is a challenging task owing to conflicts present in such systems. If not handled effectively, the conflicts can degrade the performance of the system as a whole because each individual entity may be working towards goals that sub-optimise the holistic system. A comprehensive literature review is presented in this paper to address the importance of the conflict detection and thus, the supply chain coordination. The objectives of this paper are to report and review various perspectives on supply chain conflicts, to understand and appreciate various methods for conflict detection, and to identify the gaps existing in the literature. A comprehensive tool for conflict analysis is also suggested indicating scope for further research.